Developing a bio-composite substrate using bambusa vulgaris for microwave application / Mohamad Yusof Mat Zain - Mat Zain, Mohamad Yusof (2019)
Antenna is one of the most important components in wireless communication systems. In line with the advancement of industrial technology, the development of antenna should also be improved to meet the needs of the industry especially in the field of wireless communication. There are many antennas used to fulfil the needs of wireless communication. One of the existing antennas is the patch antenna. Currently, patch antennas were developed using existing substrates such as Flame Retardant type 4 (FR-4) and Rogers. These substrates are good but they are expensive. Thus, the development of a new low cost substrate with good performance would really be significant to the communication field. Beside that, with the supportive intention to utilise the abundant natural resources, the novel of rectangular patch antenna fabricated using a new bio-composite material is presented in this study. The bio-composite material is used to serve as an alternative substance in microwave applications. The bio-composite material is made of a bamboo which is technically known as Bambusa Vulgaris and a particular polymer named as High Density Polyethylene (HDPE). In general, the bio-composite material is purposely developed as a substrate in the patch antenna application. The green composite substrate is developed through wood plastic composite (WPC) technique that involves a lot of procedures, standards, and apparatuses. 7 samples of substrates separated by different composition of elements and different filler’s (Bambusa Vulgaris) particle size were invented. The characteristics of all developed substrates were measured using several techniques and standards. All involved equipment, samples, and procedures adhered to the certified American Society for Testing and Materials (ASTM) standards. All the developed bio-composite substrates were measured their characteristics in terms of dielectric constant, loss tangent, breakdown voltage, and tensile strength. Every fabricated substrate provides unique properties which would provide big impacts in patch antenna applications. Furthermore, a patch antenna was developed using one of the developed substrates to verify the effectiveness of the bio-composite substrate in patch antenna application. Few parameters such as S-parameter and radiation pattern were measured to observe the real performance of the rectangular patch antenna developed on the bio-composite substrates. From these two major parameters, other performances of the patch antenna could be calculated and determined. Beside that, for comparison, a patch antenna was also fabricated using a selected existing substrate which is FR-4. According to the obtained results, the patch antenna developed using Bambusa Vulgaris offers better performance compared to FR-4. The patch antenna using Bambusa Vulgaris provides higher gain, wider beamwidth, and higher efficiency. All measurement results were recorded, analysed, and discussed. Beside that, further investigations on this substrate are really needed and this was also addressed. This is because to reveal other potentials of the bio-composite material in the current industry and technology.